Impact of transmission line lightning performance on an operational substation reliability considering the lightning stroke incidence angle - T. Hamel; S. Bedoui; A. Bayadi (Electrical engineering & Electromechanics)
Introduction. This study investigates substation failures caused by lightning strikes, which significantly affect operational reliability. Given the random nature of lightning strikes, a robust statistical approach is essential for accurately assessing their effects. Method. The research develops a comprehensive procedure to analyse the random distribution of non-vertical lightning strikes on transmission lines using the Monte Carlo method, a widely recognized statistical simulation technique. The goal of this work is to evaluate the performance of air-insulated substations under various lightning strike scenarios affecting the connected transmission lines. This is assessed in terms of mean time between failures (MTBF), determined by the basic insulation level of the equipment. The study incorporates both vertical and non-vertical strikes to address a critical gap in the literature, offering practical insights to enhance the reliability and safety of air-insulated substations. By considering the angle of lightning strikes, the study improves the accuracy of evaluating lightning performance using precise modelling of system components. Results. MATLAB and EMTP software were used to simulate and analyse the substation’s response to lightning-induced surges at various strike angles. The results are more representative of real-world conditions and reveal that non-vertical lightning strikes significantly reduce MTBF, underscoring the importance of advanced protective measures. Practical value. The findings highlight the necessity of accounting for the angle of lightning strikes when assessing substation reliability. References 32, table 4, figures 13.